A Temporary Haven: A Phenomenological and Psychoanalytic Comic Book on Escapism Through Media Based on Senior Highschool De La Salle University Students - Moncada, Julianna Mikaela R. (Animo Repository, 2022)
The lockdown caused by the coronavirus outbreak has generated a new normal for all. Because of the stress and anxiety caused, we tend to look for an escape from reality. Escapism is a diversion of the mind to purely imaginative recreation when the pressures of life become unbearable. It is what we turn to when faced with extreme emotions or unpleasant situations. One must ask how present society escapes when we do everything online. This study examines how De La Salle University Integrated School senior high students escape reality during a pandemic and define escapism through two frameworks—psychological, philosophical. A result of the overall research is a comic book. It will contain two different art styles called "reality" and "mindscape." Reality represents the state of the world we currently live in, while mindscape symbolizes the world we go to when escaping reality.